An Intelligent Scheme for Facial Expression Recognition - Raouzaiou, Amaryllis; Ioannou, Spiros; Karpouzis, Kostas; Tsapatsoulis, Nicolas; Kollias, Stefanos D.; Cowie, Roddy I D (My University, 2003)
This paper addresses the problem of emotion recognition in faces through an intelligent neuro-fuzzy system, which is capable of analysing facial features extracted following the MPEG-4 standard, associating these features to symbolic fuzzy predicates, and reasoning on the latter, so as to classify facial images according to the underlying emotional states. Results are presented which illustrate the capability of the developed system to analyse and recognise facial expressions in human computer interaction applications.
Keywords: Neural networks (Computer science)--Congresses